Quantification of Enhancement in Atmospheric CO2 Background Due to Indian Biospheric Fluxes and Fossil Fuel Emissions. Issue 13 (1st July 2021) - Halder, Santanu; Tiwari, Yogesh K.; Valsala, Vinu; Sreeush, M. G.; Sijikumar, S.; Janardanan, Rajesh; Maksyutov, Shamil
Abstract: Regional carbon emissions impact global atmospheric carbon dioxide (CO2 ) background concentrations. This study quantified the enhancement in the atmospheric CO2 mole fractions due to biospheric and fossil fuel fluxes from India. Sensitivity experiments using model simulations were conducted, allowing CO2 enhancement due to biospheric and fossil fuel fluxes from India to diffuse into the global atmospheric background. The areal extent of column‐averaged enhancement of 0.2 ppm and above due to Indian fluxes are spread over a larger area covering the Indian subcontinent, neighboring Asian regions, and the north Indian Ocean in all four seasons. The boundary layer CO2 enhancement due to biospheric fluxes (fossil fuel fluxes) have a maximum range of −2.6 to +1.4 ppm (1.8–2.0 ppm) most time of the year. At higher altitude, the amplitudes of enhancement are reduced from ±1.8 to ±0.6 ppm as we go up from 850 to 500 hPa due to diffusion by prevailing atmospheric dynamics and convection. With the information of the areal extent of >0.2 ppm CO2 enhancement due to Indian fluxes, we have evaluated the representativeness of satellite observations (GOSAT and OCO‐2) in capturing those enhancements. Both the satellite coverage show a similar number of observations (0.1 per day) during all seasons except for June to August, wherein the cloud screening eliminates almost all the satellite data over the region. Within this areal extent, the satellite XCO2 shows average anomalies of nearly ±2.0 ppm; it is a valuable piece of information because it is well above the retrieval uncertainty, yet capturing the potential enhancement due to fluxes from India. The study implies that the regions of enhancement greater than 0.2 ppm can be considered locations for surface observations representing Indian fluxes. Similarly, the region with enhancement greater than one ppm could be covered by satellites/airborne observations to discern enhancement in the atmospheric CO2 mole fractions due to Indian fluxes. Plain Language Summary: This study calculates the seasonal enhancement of the atmospheric CO2 concentration (in ppm) due to biospheric fluxes and fossil fuel emissions from India. The regional fluxes of fossil fuel and biospheric activities contribute to the global atmospheric CO2 within a few ppm. Using a global atmospheric tracer transport model and regional fluxes, we show that the enhancement of the atmospheric CO2 due to India's biospheric fluxes and fossil fuel emission spread over a large extent over India and surrounding regions. A tangible value of ±1.8 ppm and above can be found in most parts of India and its surrounding regions during significant seasons. The areal extent grows from the boundary layer to the upper atmosphere due to corresponding atmospheric mixing and dynamics. On the surface, the enhancement due to biospheric fluxes is about −2.6 to +1.4 ppm in all four seasons, whereas the enhancement due to fossil fuel shows about 1.8–2 ppm. The extent of discernible enhancement in the global atmospheric background due to Indian fluxes helps us understand the optimum location where all observational efforts should be made to sample Indian emission scenarios from global backgrounds. This study also points out the capability in observing the enhancement of XCO2 by the satellite over India and its surroundings. Satellite observations are crucial where the observations of atmospheric CO2 are limited to constrain the surface fluxes in the inverse modeling study. Satellite measurements can capture the enhancement except June to August when the observations are screened out for cloud contamination. Therefore, surface observations are necessary to capture the enhancement of Indian emissions in the global atmospheric CO2 background in all seasons. Key Points: Indian carbon fluxes significantly contribute to the CO2 concentrations as large as ± 2.0 ppm over India and neighboring regions throughout the year at surface level (i.e., 975 hPa) Satellites are capable of representing the XCO2 anomalies up to ± 2.0 ppm over corresponding regions; however, they have no data coverage during rainy seasons The study recommends both ground‐based and satellite/aircraft measurements of CO2 be employed to observe the larger area of Indian CO2 enhancements